ASC annual report 2015-16 (Annual report Australian Sports Commission, 2016)
The Australian Sports Commission is the Australian Government agency that develops, supports and invests in sport at all levels. It was established in 1985 and operates under the Australian Sports Commission Act 1989. The Commission`s national leadership role is achieved through three operational divisions: the Australian Institute of Sport, Participation and Sustainable Sports, and Corporate Operations. The Australian Sports Commission forms part of the Health portfolio. This report has been prepared in accordance with parliamentary reporting and legislative requirements and provides details of the Australian Sports Commission`s (ASC) performance and operations for the financial year ending 30 June 2016. This report details how effective the ASC has been at achieving its outcomes for the year as outlined in the ASC 2015-19 Corporate Plan and the 2015-16 Portfolio Budget Statements.